Successful preparation of BaCo0.5Fe0.5O3–δ cathode oxide by rapidly cooling allowing for high-performance proton-conducting solid oxide fuel cells - Yanru Yin; Yanbin Zhou; Yueyuan Gu; Lei Bi (Journal of Advanced Ceramics, 2023)
A pure phase BaCo0.5Fe0.5O3–δ (BCF), which cannot be obtained before, is successfully prepared in this study by using the calcination method with a rapid cooling procedure. The successful preparation of BCF allows the evaluation of this material as a cathode for proton-conducting solid oxide fuel cells (H-SOFCs) for the first time. An H-SOFC using the BCF cathode achieves an encouraging fuel cell performance of 2012 mW·cm–2 at 700 ℃, two-fold higher than that of a similar cell using the classical high-performance Ba0.5Sr0.5Co0.8Fe0.2O3–δ (BSCF) cathode. First-principles calculations reveal the mechanism for the performance enhancement, indicating that the new BCF cathode significantly lowers the energy barriers in the oxygen reduction reaction (ORR) compared with the BSCF cathode. Therefore, improved cathode performance and fuel cell output are obtained for the BCF cell. The fuel cell using the BCF cathode also shows excellent long-term stability that can work stably for nearly 900 h without noticeable degradations. The fuel cell performance and long-term stability of the current BCF cell are superior to most of the H-SOFCs reported in previous reports, suggesting that BCF is a promising cathode for H-SOFCs.